2013
DOI: 10.1021/ef401374y
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on Measurement of Temperature and Emissivity of Municipal Solid Waste (MSW) Combustion by Spectral Analysis and Image Processing in Visible Spectrum

Abstract: This paper presents an experimental investigation on the measurement of temperature and emissivity in a 46 ton/ h Municipal Solid Waste (MSW) incinerator using a spectrometer system and a flame image detection system. The spectroscopy analysis shows that strong Na (590 nm) and K (767 nm) emission occurs in the visible spectrum of the flame in the MSW incinerator, which demonstrates a typical nongray property of radiation. The two-color method is used to calculate the temperature and emissivity of the flame fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…To quantitatively analyze the spectra of the flame's spontaneous emission, it is necessary to calibrate the profile of the spectral radiation intensities I(λ) along the wavelength. As described in [14,15,17], a blackbody furnace was used to obtain the calibration coefficients k(λ) = I b (λ)/S b (λ). Figure 2 shows the profiles of k(λ) within the wavelength range from 500 nm to 900 nm at four temperatures: 1273, 1373, 1473, and 1573 K. It can be seen that profiles of the calibration coefficients at different blackbody temperatures were consistent with each other; thus, it can be concluded that the calibration coefficients remained independent of temperature.…”
Section: Measurement Principlementioning
confidence: 99%
See 1 more Smart Citation
“…To quantitatively analyze the spectra of the flame's spontaneous emission, it is necessary to calibrate the profile of the spectral radiation intensities I(λ) along the wavelength. As described in [14,15,17], a blackbody furnace was used to obtain the calibration coefficients k(λ) = I b (λ)/S b (λ). Figure 2 shows the profiles of k(λ) within the wavelength range from 500 nm to 900 nm at four temperatures: 1273, 1373, 1473, and 1573 K. It can be seen that profiles of the calibration coefficients at different blackbody temperatures were consistent with each other; thus, it can be concluded that the calibration coefficients remained independent of temperature.…”
Section: Measurement Principlementioning
confidence: 99%
“…The spontaneous emission spectra of flames contain continuous spectra from the blackbody radiation of solid particles (e.g., soot, char, or ash particles); from the band spectra produced by the radiation of gas molecules (e.g., CO 2 or H 2 O); from the chemiluminescence of excited radicals (e.g., OH, CH, or C 2 ); and from the line spectra of free atoms (e.g., alkalis or alkaline earth metals) [10]. Based on the measurement and analysis of the spontaneous emission spectra of flames, FES has been proposed to determine equivalence ratios [9], to monitor flame stoichiometry [9,11] and to calculate flame temperatures in a natural gas-fired furnace [12], a pulverized coal-fired furnace [13,14], a gasification facility [15], an aluminum flame [16], and even an MSW incinerator [17]. For the flame of the MSW incinerator, strong characteristic emission lines of Na and K are observed in the visible spectra in the experiments, and more studies are needed to know if this type spectrum could be used for measurement temperature, while related works are relatively few in number.…”
Section: Introductionmentioning
confidence: 99%
“…To further characterize the cameras, calibration was required. In a previous study on image processing techniques, the R, G, and B data of a pixel in the color digital camera are not proportional to the monochromatic radiative intensities because of the broad spectral response spectra of the R, G, and B bands of the color camera [16][17][18][19]. To characterize the relative spectral response of the camera, an experiment similar to Ref.…”
Section: Calibrations Of the Digital Color Cameramentioning
confidence: 99%
“…Kotzagianni et al [11] applied laser-induced breakdown spectroscopy (LIBS) for uniform methane-air mixtures spanning a wide range of compositions and for turbulent non-premixed and premixed flames. Flame image processing techniques based on a digital camera used for pyrometric measurements have been used to measure flame temperature and radiative properties [12][13][14][15][16][17][18][19][20][21]. In a previous study [18], a color digital camera was used to capture the flame image in visible spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…However, expensive equipment and complex optical systems are required; therefore, this approach is not easily applied to industrial furnaces. Image processing techniques, based on a tri-chromatic signal of the image and using the two-color method, have been widely used for temperature measurements of furnace flames [7][8][9][10]. The emission from emitters at two wavelengths is utilized to calculate the temperature and emissivity in image processing techniques.…”
Section: Introductionmentioning
confidence: 99%